Integration of multiple forms in contemporary Nepali arts - Sharma, Yam Prasad (Journal of Fine Arts Campus, 2025)
Contemporary Nepali arts integrate contents, forms and techniques of arts from multiple cultures and countries. They reconcile western forms and native Nepali creative traditions. Such ambivalent attitude creates native varieties contemporary context. The appropriation of multiple forms presents visual inter-textuality in the artworks. The artworks also blur the boundary of various art genres like poetry, photography, theatre, painting, sculpture and music. The works present inter- art relationship and intertextuality of multiple disciplines and genres of arts. Contents and forms from different cultures are apparent in Nepali arts. Such cross-currents encounter and interact to creating new forms. Due to the presence of multiple voices, their significance is plural. Globalization has brought fleeting, and ever-changing art influences unsettling representational modes in creativity. Intertextual and intergeneric arts have blurred the boundaries of cultures and creations. Hindu and Buddhist myths and traditions have been visually presented with western techniques and forms. The cross-cultural interflow provides a sense of strange aesthetic pleasure.